Piscine mycobacteriosis in the ornamental fish trade in Trinidad and Tobago - Ayanna Carla N. Phillips Savage; Lemar Blake; Rod Suepaul; O’Shane McHugh; Ray Rodgers; Calvern Thomas; Christopher Oura; Esteban Soto (Journal of Fish Diseases, 2022)
The freshwater ornamental fish trade represents a major contributor to the livelihoods of many producers in Trinidad and Tobago, with stocks destined for local, regional and international markets. A review of clinical cases presented to the Aquatic Animal Health Unit at the University of the West Indies, School of Veterinary Medicine for the period September 2010 to December 2012 suggested that piscine mycobacteriosis may be widespread throughout the local ornamental fish industry. Thus, to determine the prevalence of mycobacteriosis in ornamental fish sold in pet stores, a total of 122 specimens were sourced from 24 retail suppliers across Trinidad. Fish were killed and internal organs were examined for lesions suggestive of granulomas. All wet‐mount slides were acid‐fast stained, regardless of the presence or absence of observed granuloma‐like lesions. Histological analysis was performed on one randomly selected whole specimen from each facility. Mycobacterium sp. was identified using real‐time PCR detecting the 16S rRNA gene in tissue samples. Associations between parasitism, facility biosecurity and presence of positive animals were determined. The prevalence of Mycobacterium sp. infection was 61 ± 7% (74/122), with positive specimens being acquired from 54.2% (13/24) of facilities examined. Further, 100% of facilities did not employ optimum biosecurity measures.